Rituximab mitoxantrone: comparing effectiveness and safety in advanced relapsing multiple sclerosis - Tobias Zrzavy; Esther Daniels; Niklas Stuka; Dennis Weber; Alexander Winkelmann; Helmut Rauschka; Michael Hecker; Fahmy Aboulenein-Djamshidian; Stefanie Meister; Fritz Leutmezer; Thomas Berger; Gabriel Bsteh; et al. (SAGE Publishing, 2021)
Background: Rituximab (RTX), a CD20 depleting agent, is a frequently used off-label treatment for multiple sclerosis (MS), while mitoxantrone (MTX) is approved, albeit rarely used for active relapsing MS (RMS). However, observational data comparing RTX and MTX effectiveness and safety are scarce. Objective: We aimed to compare effectiveness and safety of MTX and RTX in patients with active RMS. Methods: From combined retrospective clinical data of three MS centers, we selected patients who had received at least one infusion of RTX or MTX and had at least a 6-month clinical follow-up available. Treatment groups were compared by propensity score (PS)-adjusted regression and inverse PS-weighted generalized estimated equation models regarding disability progression, relapse activity, and adverse events (AEs). Results: We included 292 RMS patients (mean age 41.8 years, 71.6% female) who received RTX (119 patients, mean age 36.8 years, 74.8% female) or MTX (173 patients mean age 45.3 years, 69.4% female). Using both PS methods, we did not find a significant effect favoring RTX or MTX treatment regarding the probability of disability worsening or relapse occurrence. However, RTX treatment was associated with a significantly lower probability of severe AEs and AEs. Conclusions: RTX shows comparable effectiveness but a favorable safety profile compared with MTX in active RMS.